2015
DOI: 10.1186/s13058-015-0550-y
|View full text |Cite
|
Sign up to set email alerts
|

Gene-expression molecular subtyping of triple-negative breast cancer tumours: importance of immune response

Abstract: IntroductionTriple-negative breast cancers need to be refined in order to identify therapeutic subgroups of patients.MethodsWe conducted an unsupervised analysis of microarray gene-expression profiles of 107 triple-negative breast cancer patients and undertook robust functional annotation of the molecular entities found by means of numerous approaches including immunohistochemistry and gene-expression signatures. A triple-negative external cohort (n = 87) was used for validation.ResultsFuzzy clustering separat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
209
2
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 255 publications
(246 citation statements)
references
References 57 publications
(58 reference statements)
14
209
2
12
Order By: Relevance
“…In this section, we further established a consensus on the description of basal-like subgroups (Basal I and Basal II) by comparing our results with other achievements across the literature [10, 1921, 31], as per the focus of each study. Notably, most of them have centred on the classification of triple-negative entities, a more heterogeneous group than basal-like.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In this section, we further established a consensus on the description of basal-like subgroups (Basal I and Basal II) by comparing our results with other achievements across the literature [10, 1921, 31], as per the focus of each study. Notably, most of them have centred on the classification of triple-negative entities, a more heterogeneous group than basal-like.…”
Section: Discussionmentioning
confidence: 94%
“…Recent investigation of TNBCs pointed to the existence of intrinsic basal-like subtypes, with distinct molecular patterns [1921]. The stratification performed and described by Lehmann et al (2011) [19] revealed the involvement of enriched cell cycle and cell division components in Basal-like 1 (BL1); growth factor signalling, glycolisis and gluconeogenesis pathways in Basal-like 2 (BL2); and immune cell processes in Immunomodulatory (IM).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Gene expression studies of BC-adjacent tissues showed that the TNBC microenvironment had increased expression of genes involved in inflammation 14 and revealed further subtypes, some with a low immune response defined by a minimal T cell infiltrate and effector function, and high frequency of suppressive M2-like macrophages, and others with a high immune response and low frequency of M2-like macrophages. 15 These data imply that communication between tumor cells and other cells in cancer-adjacent tissue contributes to BC progression and/or metastasizing potential; the same is likely to be true for Luminal B BC (Fig. 1).…”
Section: Breast Cancer and Immunitymentioning
confidence: 73%
“…76 In summary, we suggest that evaluation of markers of immune suppression has prognostic value in luminal B BC. To avoid confounding factors in assessment of the role of the immune system it is vital that the study cohort be carefully selected to minimize variation in Luminal B BC patients' immune systems, e.g., restricted age range 15 and absence of comorbid conditions which may affect immune status. Further, utilization of international standardized criteria for histological analysis is vital for interpretation of the results.…”
mentioning
confidence: 99%